The transcription factor MITF is a critical regulator of GPNMB expression in dendritic cells. Issue 1 (December 2015) - Gutknecht, Michael; Geiger, Julian; Joas, Simone; Dörfel, Daniela; Salih, Helmut; Müller, Martin; Grünebach, Frank; Rittig, Susanne
Abstract Background Dendritic cells (DC) are the most potent antigen-presenting cells (APC) with the unique ability to activate naïve T cells and to initiate and maintain primary immune responses. Immunosuppressive and anti-inflammatory stimuli on DC such as the cytokine IL-10 suppress the activity of the transcription factor NF-κB what results in downregulation of costimulatory molecules, MHC and cytokine production. Glycoprotein NMB (GPNMB) is a transmembrane protein, which acts as a coinhibitory molecule strongly inhibiting T cell responses if present on APC. Interestingly, its expression on human monocyte-derived dendritic cells (moDC) is dramatically upregulated upon treatment with IL-10 but also by the BCR-ABL tyrosine kinase inhibitors (TKI) imatinib, nilotinib or dasatinib used for the treatment of chronic myeloid leukemia (CML). However, the molecular mechanisms responsible for GPNMB overexpression are yet unknown. Results The immunosuppressive cytokine IL-10 and the BCR-ABL TKI imatinib or nilotinib, that were examined here, concordantly inhibit the PI3K/Akt signaling pathway, thereby activating the downstream serine/threonine protein kinase GSK3ß, and subsequently the microphthalmia-associated transcription factor (MITF) that is phosphorylated and translocated into the nucleus. Treatment of moDC with a small molecule inhibitor of MITF activity reduced the expression of GPNMB at the level of mRNA and protein, indicating that GPNMB expression is in fact facilitated by MITF activation. In line with these findings, PI3K/Akt inhibition was found to result in GPNMB overexpression accompanied by reduced stimulatory capacity of moDC in mixed lymphocyte reactions (MLR) with allogeneic T cells that could be restored by addition of the GPNMB T cell ligand syndecan-4 (SD-4). Conclusions In summary, imatinib, nilotinib or IL-10 congruently inhibit the PI3K/Akt signaling pathway thereby activating MITF in moDC, resulting in a tolerogenic phenotype. These findings extend current knowledge on the molecular mechanisms balancing activating and inhibitory signals in human DC and may facilitate the targeted manipulation of T cell responses in the context of DC-based immunotherapeutic interventions.